2020
DOI: 10.1029/2020gl087860
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Nighttime Production of Organic Nitrates During SEAC4RS, FRAPPÉ, and KORUS‐AQ

Abstract: Organic nitrates (RONO2) are an important NOx sink. In warm, rural environments dominated by biogenic emissions, nocturnal NO3‐initiated production of RONO2 is competitive with daytime OH‐initiated RONO2 production. However, in urban areas, OH‐initiated production of RONO2 has been assumed dominant and NO3‐initiated production considered negligible. We show evidence for nighttime RONO2 production similar in magnitude to daytime production during three aircraft campaigns in chemically distinct summertime enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…One possible explanation was the different formation mechanisms of LO-OOA in summer and winter. Although LO-OOA was dominantly from oxidation of anthropogenic VOCs, for example, organic nitrates from NO 3 oxidation at nighttime in winter due to low emissions of biogenic VOCs, it could have a large contribution from oxidation of biogenic VOCs in summer . Indeed, previous studies found that the monoterpene- and sesquiterpene-derived SOA decreased and the anthropogenic SOA from toluene oxidation increased with the increase in the height in the city …”
Section: Resultsmentioning
confidence: 97%
“…One possible explanation was the different formation mechanisms of LO-OOA in summer and winter. Although LO-OOA was dominantly from oxidation of anthropogenic VOCs, for example, organic nitrates from NO 3 oxidation at nighttime in winter due to low emissions of biogenic VOCs, it could have a large contribution from oxidation of biogenic VOCs in summer . Indeed, previous studies found that the monoterpene- and sesquiterpene-derived SOA decreased and the anthropogenic SOA from toluene oxidation increased with the increase in the height in the city …”
Section: Resultsmentioning
confidence: 97%
“…Hence, we inferred that the parallel increases of aerosol ON and IN during nighttime was most likely a result of the nocturnal chemistry involving NO 3 radical. It has been long realized that organic nitrates contribute importantly to OA mass, particularly those formed during nighttime involving the reactions between alkenes and NO 3 radical (Kenagy et al., 2020; Perring et al., 2013; Rollins et al., 2012; Xu et al., 2021). However, observation studies of organic nitrates in urban atmospheres are limited, especially in the megacities of China (Huang et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Kenagy et al. ( 2020 ) suggest that organic nitrate production from NO 3 ‐initiated VOC oxidation at night is comparable to that from OH‐initiated VOC oxidation during the day in the Southeast US. Further evaluation of how well CESM/CAM‐chem represents the boundary layer and chemistry at night may also be needed to fully understand this organic nitrate model bias.…”
Section: Resultsmentioning
confidence: 99%